The Effect of Person Job-Fit and Internal Service Quality on Job Performance Through Job Satisfaction at 3-Star Hotel Employees in Surabaya - Yuniarto, Antonius; Setiawan, Shieren Valencia (Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
The goal of this research is to determine and evaluate the impact of person-job fit and internal service quality on job performance as assessed by work satisfaction. Staff from Surabaya's three-star hotels made up the sample for this study. There were 145 responses in the sample. The sampling approach used in this study was purposive. This survey's respondents were 17 years or older, had at least one year of work experience, and worked in Surabaya's three-star hotels. The core data for this study were gathered by giving questionnaires on printed questionnaire sheets. This study used Structural Equation Modeling with SmartPLS as its data analysis method. The results of the study prove that person-job fit significantly influences job satisfaction, internal service quality significantly influences job satisfaction, job satisfaction significantly influences job performance, person-job fit significantly influences job performance through job satisfaction, and internal service quality significantly influences job performance through job satisfaction. Keywords: Person Job-Fit, Internal Service Quality, Job Satisfaction, Job Performance, Hotel.